2016
DOI: 10.1542/peds.2015-2143
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cerebral Vasospasm and Childhood Arterial Ischemic Stroke After Intrathecal Cytarabine

Abstract: We report on 2 patients who developed widespread cerebral vasospasm and arterial ischemic strokes (AIS) after application of intrathecal (IT) cytarabine. In a 3-year-old child with acute lymphoblastic leukemia (ALL), left leg weakness, hyperreflexia, and clonus were noted 4 days after her first dose of IT cytarabine during the induction phase of her chemotherapy. Cerebral MRI revealed multiple acute cerebral ischemic infarcts and widespread cerebral vasospasm. A 5-year-old girl complained of right arm and leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Pediatric cases of nonaneurysmal, non-TBI vasospasm have been reported following open tumor resection [13-16] and administration of certain chemotherapies [17, 18] (Table 1). These patients presented between POD5 and POD12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric cases of nonaneurysmal, non-TBI vasospasm have been reported following open tumor resection [13-16] and administration of certain chemotherapies [17, 18] (Table 1). These patients presented between POD5 and POD12.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes ranged from severe disability to full recovery. All authors encourage prompt diagnosis and treatment, as the high morbidity and mortality reported may be in part related to a delay in diagnosis [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Generally, inflammatory arteriopathies such as focal cerebral arteriopathy, inflammatory subtype (FCA i ) and primary angiitis of the central nervous system (PACNS) demonstrate circumferential enhancement of the vessel wall with periadventitial involvement, whereas noninflammatory arteriopathies such as reversible cerebral vasoconstriction syndrome more often show little to no enhancement. 9,11,12 Reported VWI findings in dissection include eccentric mural enhancement related to inflammation, and variable T1 hyperintensity related to intramural hematoma. 13 Evolution of signal intensity within the intramural hematoma over time has been described in patients with extracranial arterial dissections, with highest lesion conspicuity occurring in the late subacute period 7 to 14 days after lesion initiation.…”
Section: Vessel Wall Imagingmentioning
confidence: 99%
“… 1 Less commonly, the use of chemotherapeutic agents can precipitate RCVS and intrathecal cytarabine has been reported as a rare causative agent in the pediatric population. 2 , 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%